Análisis de rentabilidad y estudio del capital de Trabajo de la cooperativa de ahorro y crédito jardin Azuayo de la ciudad de Gualaquiza, provincia de Morona santiago, desde el 01 de enero al 31 de Diciembre del 2013 - Arias Chica, Jeny Maritza (2014)
This research "PROFITABILITY ANALYSIS AND STUDY OF WORKING CAPITAL Creditunion " GARDEN Azuayo " CITY Gualaquiza, Morona Santiago province, FROM 01 JANUARY TO 31 DECEMBER 2013 ", is intended to implementcertainfinancial ratios to determine thedevelopment of theaforementionedcooperativestudy and to recommenditsimprovement, islendinginstitutioniscommitted to servingcreditunions in thecity of Gualaquizathesamethatislocated in theprovince of Morona Santiago, themainfocuswasdirected to conduct a costbenefitanalysis and study of working capital, whichwillrevealtheirprofitability, liquidity, solvency, profitabilityindebtedness and debt capital of thecooperative, fordecision -making and compliancegoals and businessobjectives. Note thatthisstudyforbetterunderstandingconsists of a titlewhichrefers to whatisanalyzed and investigated , summarized in therelevantparts of theworkconducted , introduction, whichindicatestheimportance of thestudy to theaforementionedSavings and CreditCooperative , Garden Azuayo , literaturereview , whichprovidesthetheoreticalfoundation , whichincludesthesamebasicconcepts and principlesnecessary to understand and comprehendtheimportance of ananalysis of profitability and working capital ; thenthepresentation and discussion of results in whichtheargument of theCooperativeSavings and Credit Garden Azuayo describedoccursalsopresentresultswhichcomprisestheanalysis and interpretationof informationobtainedthroughtheapplication of certainindicesincludedfinancial and profitability ( 40.29 ) , liquidity ( 1.12 ) , strength (0.95 ) , outsideworking capital ( 0.02 ) and administrativemanagementindex ( 0.011 ) , as well as the use of methods , techniques and procedureswerethesame as necessaryforthefulfillment of objectivesusingforthisthefinancialstatements of thecooperativestudywhichcouldmeetassets $ ( 9'783.781,65 ) and theirimpactontheprofitability of theCooperativeSavings and Credit , Garden Azuayo and likewiseliabilities $ ( 9'289.167,17 ) and equity $ ( 494,614.48 ) whichhighlightsthemostimportantdebtaccounts. Theincomestatement in whichtheycouldclearlyseethe total revenue $ ( 1'206.177, 97) and expense $ ( 10'069.008,18 ) and theincomegeneratedbyeconomicactivityamountingitwasalsoanalyzed to $ 199.269,79. Withallthebackgrounddescribedabove comes a proposalforthefinancialinstitutionthrough a study of itsfinancial and operationalstructure, besides a study of itsfinancialstatements and incomestatementsis done , likewise a study of itsadministrative and operationalsituationdevelopedwheresignificantresultswereobtained as working capital thesamewhichis $ 1'011.786,12 thatwillcontribute to theproperprocess and development of theCooperativeSavings and Credit Azuayo Garden. At studyperformedtherespectiveconclusions and recommendations are set thesamethatwillcontribute to improvetheeconomic ,financial and administrativemanagement of theCooperativeSavings and Credit Garden Azuayo , allowingthecontinuedgrowth of thesame.